Exploring Post-Traumatic Growth in Child Survivors of the Semeru Eruption: The Role of Religious and Social Support in Recovery - Hanafi, Husni; Hidayah, Nur; Rusmana, Nandang; Asrowi; Apriani, Rizka; Saputra, Nur Mega Aris; ilmi, Achmad Miftachul; Kurniawan, Nanda Alfan; Fifi Khoirul Fitriyah (Universitas Nahdlatul Ulama Surabaya, 2024)
The Semeru eruption in 2021 had a traumatic impact for almost a year. People there live with anxiety and traumatic symptoms, including Children. This study aims to identify the post-traumatic conditions of children in this recovery stage. This research was qualitative research with a phenomenological design. The main subjects were 94 children in the Supiturang village, Lumajang, the closest village to Mount Semeru. Data were collected by observing and interviewing the children. Triangulation of data was carried out by in-depth interviews with six adults (the parents, the village elder, and the teacher of some children). The results showed that (1) anxiety and traumatic symptoms in some children were relatively high; (2) there was an increase in social support from the community for the children, and (3) religious activities made a deeper meaning in the children's recovery process. The results of this study underline that social support and religious approaches as the main factors in children's recovery process. The results of this study underlie the need for alternative treatments based on local wisdom with a collective and religious approach so that the community can do it independently and sustainably for the children.